Secondary Controller for Parallel Operated Inverters in Islanded Microgrid Using Variable Structure Control Strategy - Hammadi Mjily, Anwer; Yasir Naser, Hayder; H. Jasim, Basil (Iraqi Journal for Electrical and Electronic Engineering, 2026)
This paper presents a novel linear variable structure secondary controller for islanded Microgrid driven by voltage source inverters. The main control stretchy depends on a low pass filter based frequency restoration. The proposed control strategy solves the problem of trade of between accurate frequency restoration and active power sharing accuracy by using variable structure controller. A bank of low pass filters with different parameter values are used instead of single fixed parameter controller. An efficient algorithm is designed to switch between the compensators in the bank to achieve the two objectives, namely accurate frequency restoration and fast power sharing. The switching algorithm uses event driven protocol to trigger its activation until reaching steady state and then staying stand by for the next event where the event is active power change. Simulation results shows an excellent result.